Mobile in learning: Enhancement of information and communication technologies - P George, Jossy; M, Vinay (International Journal of Engineering and Technology, 2018)
The technological advancement in the world has changed the people’s life. The people view point towards the usage of technologies in different fields like business, tourism, communication, education etc. has changed. Mobile learning can give flexible learning environment for the user. It can also increase the participant number in the online teaching learning process. This paper discusses about the effectiveness of the current technologies used in higher education system. It profiles the advantages of using mobile in accessing the university central system for teaching and learning. It also discusses about mobile digital book with augmentation, which can be used to improve the teaching and learning process of the different departments in the university